Activity-Based Costing Diffusion, Strategy and Organizational Performance: Evidence from Iran - Miryazdi, Seyed Mahmoud; Jusoh, Ruzita (Asian Journal of Accounting Perspectives, 2015)
While management accounting literature has shown substantial evidence on ABC adoption and implementation within the Western context, this study attempted to provide some insight into the ABC diffusion stages within the Iranian context. Using a revised four-stage model in measuring activity-based costing (ABC) diffusion, this study examines the performance consequence of ABC diffusion together with its relationship with Miles and Snow (1978) strategic types. From purposeful sampling of manufacturing companies listed in the Tehran Stock Exchange, a total of 400 survey questionnaires sent to these companies where 300 usable completed questionnaires were returned and analysed. Hypotheses were tested using ordinal logistic regression and ANOVA analyses. The results showed that firms at higher ABC diffusion stages have better levels of organizational performance than firms at the lower ABC diffusion stages. In addition, the analyzer strategy was a significant factor in determining a firm’s decision to go to higher ABC diffusion stages.